Development of a Novel Escherichia coli–Kocuria Shuttle Vector Using the Cryptic pKPAL3 Plasmid from K. palustris IPUFS-1 and Its Utilization in Producing Enantiopure (S)-Styrene Oxide - Toda, Hiroshi; Itoh, Nobuya (Frontiers in Microbiology, 2017)
The novel cryptic pKPAL3 plasmid was isolated from the Gram-positive microorganism Kocuria palustris IPUFS-1 and characterized in detail. pKPAL3 is a circular plasmid that is 4,443 bp in length. Open reading frame (ORF) and homology search analyses indicated that pKPAL3 possesses four ORFs; however, there were no replication protein coding genes predicted in the plasmid. Instead, there were two nucleotide sequence regions that showed significant identities with untranslated regions of K. rhizophila DC2201 (NBRC 103217) genomic sequences, and these sequences were essential for autonomous replication of pKPAL3 in Kocuria cells. Based on these findings, we constructed the novel Escherichia coli–Kocuria shuttle vectors pKITE301 (kanamycin resistant) and pKITE303 (thiostrepton resistant) from pKPAL3. The copy numbers of the constructed shuttle vectors were estimated to be 20 per cell, and they exhibited low segregation stability in Kocuria transformant cells in the absence of antibiotics. Moreover, constructed vectors showed compatibility with the other K. rhizophila shuttle vector pKITE103. We successfully expressed multiple heterologous genes, including the styrene monooxygenase gene from Rhodococcus sp. ST-10 (rhsmo) and alcohol dehydrogenase gene from Leifsonia sp. S749 (lsadh), in K. rhizophila DC2201 using the pKITE301P and pKITE103P vectors under the control of the glyceraldehyde 3-phosphate dehydrogenase (gapdh) promotor. The RhSMO–LSADH co-expressing K. rhizophila was used as a biocatalyst in an organic solvent–water biphasic reaction system to efficiently convert styrene into (S)-styrene oxide with 99% ee in the presence of 2-propanol as a hydrogen donor. The product concentration of the reaction in the organic solvent reached 235 mM after 30 h under optimum conditions. Thus, we demonstrated that this novel shuttle vector is useful for developing biocatalysts based on organic solvent-tolerant Kocuria cells.